2017
DOI: 10.1039/c7ce01717k
|View full text |Cite
|
Sign up to set email alerts
|

Structural aspects of partial solid solution formation: two crystalline modifications of a chiral derivative of 1,5-dihydro-2H-pyrrol-2-one under consideration

Abstract: The purposeful change of crystallization conditions for rac-3-chloro-5-hydroxy-1-(4-methylbenzyl)-4-[(4-methylphenyl)sulfanyl]-1,5-dihydro-2H-pyrrol-2-one 1 leads to two different crystal modifications, namely, a racemic compound in the triclinic space group P1 with Z′ = 1 (α-1) and a partial solid solution based on a racemic compound in the monoclinic space group P2 1 with Z′ = 4 (β-1). The first modification, α-1, is characterized by a higher density of the molecular packing in the crystal, while the second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 41 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Some of these variations in the phenyl group orientations are due to molecular positions C and D being able to statistically accommodate molecules of opposite chiralityin other words, the same molecular position can be occupied by either the (R)-enantiomer or the (S)-enantiomer. A similar situation was recently described by Lodochnikova and Fayzullin with collaborators 23 for a racemic 1,5-dihydro-2H-pyrrol-2-one derivative that forms a partial solid solution.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…Some of these variations in the phenyl group orientations are due to molecular positions C and D being able to statistically accommodate molecules of opposite chiralityin other words, the same molecular position can be occupied by either the (R)-enantiomer or the (S)-enantiomer. A similar situation was recently described by Lodochnikova and Fayzullin with collaborators 23 for a racemic 1,5-dihydro-2H-pyrrol-2-one derivative that forms a partial solid solution.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…At the same time, in the crystal of monoclinic 6c , the main supramolecular associate is a heterochiral chain along the glide plane (Figure d). Among previously studied racemic compounds of pyrrolin-2-one thioethers, which are usually arranged by 0D centrosymmetric heterochiral H-bonded dimers, crystal 6c is the first repetitive showing a 1D heterochiral chain.…”
Section: Resultsmentioning
confidence: 99%
“…First, for rac-3-chloro-5-hydroxy-1-(4-methylbenzyl)-4-[(4methylphenyl)sulfanyl]-1,5-dihydro-2H-pyrrol-2-one (1), we discovered a pair of synthon polymorphs. 16 The targeted change of crystallization conditions for thioether 1 leads to two different crystal modifications, namely, a racemic compound (P1̅ , Z′ = 1) and racemic compound-based partial solid solution (P2 1 , Z′ = 4). In the first case, a dimeric crystal formative motif is realized, while, in the second case, an Hbonded chain is formed.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In 2000, Coquerel published a review describing in detail the thermodynamic features of the heterogeneous equilibria between condensed phases in enantiomer binary systems . Then, Kaemmerer et al reported the feasibility of the chiral resolution of the polymorphs of malic acid enantiomers and its partial solid solution, and Lodochnikova et al described the structural attributes involved in the formation of a partial SSEs from the racemic 3-chloro-5-hydroxy-1-(4-methylbenzyl)-4-[(4-methylphenyl)­sulfanyl]-1,5-dihydro-2 H -pyrrol-2-one . Bredikhin et al.…”
Section: Introductionmentioning
confidence: 99%
“…24 Then, Kaemmerer et al reported the feasibility of the chiral resolution of the polymorphs of malic acid enantiomers and its partial solid solution, 25 and Lodochnikova et al described the structural attributes involved in the formation of a partial SSEs from the racemic 3-chloro-5-hydroxy-1-(4-methylbenzyl)-4-[(4-methylphenyl)sulfanyl]-1,5-dihydro-2H-pyrrol-2-one. 26 Bredikhin et al in their two recent investigations prepared and characterized partial and continuous SSEs. In the first publication, 27 they described the thermochemical properties of chiral API timolol maleate which behaves as a continuous SSEs, while in the second one, 28 his group reported the phase behavior of chiral para-methoxyphenyl glycerol ether and its ability to form continuous and partial solid solutions.…”
Section: Introductionmentioning
confidence: 99%